Pengaruh Perendaman Daging Sapi dengan Ekstrak Buah Nanas terhadap Kualitas Fisik Daging Sapi Brahman Cross - Harissatria; Dara Surtina; Okta Dia Melsa (Jurnal Peternakan Mahaputra, 2021)
This study aims to determine the effect of soaking Brahman cross beef with pineapple fruit extract on pH, water holding capacity, and cooking loss. The material used in this study was 1.6 kg Brahman cross beef brisket section aged 5 years. The design used was a completely randomized design (CRD) with immersion treatment (minute) with pineapple fruit extract (P0=0, P1=15, P2=30, P3=45) and 4 replications. The variables measured were pH, water holding capacity and cooking loss. The mean obtained for pH is P0=5.75; P1=5.50; P2=5.45; and P3=5,40 for water holding capacity P0=14,61; P1=21.30; P2=22.91; and P3=24.21 while for cooking loss P0=32.92; P1=21.30; P2=47.06; and P3=44.30. From the results of this study, it can be concluded that the length of soaking meat with pineapple extract gave a very significant difference (P<0.01) to the pH value and cooking loss and not significantly different (P>0.05) to the water holding capacity.